2D Electron Gas at the Interface of Atomic‐Layer‐Deposited Al2O3/TiO2 on SrTiO3 Single Crystal Substrate. (21st October 2018) - Lee, Hyun Jae; Moon, Taehwan; An, Cheol Hyun; Hwang, Cheol Seong
Abstract: The presence of 2D electron gas (2DEG) at the interface between an amorphous Al2 O3 ( a ‐AO) thin film and an anatase TiO2 (TO) thin film is demonstrated. The a ‐AO and TO thin films are prepared via atomic layer deposition on a SrTiO3 (STO) single crystal substrate. The reduction of the TO surface during the a ‐AO deposition produces oxygen vacancies, which are effective electron donors. The systematic analysis of the physical properties of the TO layer reveals that the crystallinity of the TO layer affects the conductivity, carrier concentration and the mobility of the 2DEG, and also the critical a ‐AO thickness, which is the minimum thickness for exhibiting the apparent conductivity. The 2DEG between the a ‐AO and the sufficiently thick TO layer exhibits an almost two‐orders‐of‐magnitude‐higher carrier concentration (≈10 14 cm ‐2 ) than the previously reported 2DEG at a ‐AO/STO, while the mobility (≈10° cm 2 V ‐1 s ‐1 ) is relatively low. Also, angle‐resolved X‐ray photoelectron spectroscopy elucidates the spatial distribution and atomic ratio of the reduced Ti ions. Due to the increasing fraction of the anatase phase in the TO layer, the oxygen vacancies are prone to ionize, and the carriers are better confined to the interface, making them more 2DEG‐like. Abstract : 2D electron gas at the atomic‐layer‐deposited Al2 O3 /TiO2 interface on a SrTiO3 substrate is introduced. The collaboration between the physical (X‐ray diffractometry) and electrical (Hall measurement) characterization indicates that the conductivity of the interface is associated with the anatase‐phase ratio in the TiO2 layer. The angle‐resolved X‐ray photoelectron spectroscopy results reveal that the carrier becomes more localized with increasing crystallinity.